PERBEDAAN SISTEM BROODING KONVENSIONAL DAN SISTEM BROODING THERMOS TERHADAP RESPON FISIOLOGIS BROILER - Isnaini Novi Hapsari; Purnama Edy Santosa; Rr. Riyanti (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
The purpose of the research was knowing of difference between conventional and thermos system brooding to respiration rate, heart beat rate, rectal temperature of broiler. This research was hold on 2015 December in Jati Agung, South Lampung. Two thousand DOC of broiler was used in that brooding system, and was taked 3,5 % as sample. Result of data apllying t-student test in real standart 5 %. The result of research refers to conventional brooding and thermos system give not significant effect to respiration rate, heart beat rate, and rectal temperature of broiler on 10 and 20 days. Keywords : Broiler, Physiology Response, Brooding Conventional System, Brooding Thermos System